(untitled) (Journal of Universal Science Research, 2025)
This article explores the biological nature of biostimulators and their impact on human physiological processes, including their natural and synthetic sources, their importance in clinical practice, and key aspects of their use. Special attention is given to how biostimulators influence the immune system, cellular regeneration, energy metabolism, and the aging process. The article underscores the strategic role these substances play in restoring health, preventing disease, and supporting the body’s natural defense mechanisms.